Science Literacy Skills of Prospective Primary Education Teachers: Challenges in the 21st Century - Sari, Rita; Indra Fajar Nurdin; Sigit Prasetyo; Lailla Hidayatul Amin; Daluti Delimanugari; Muhammad Fikri Abdun Nasir (International Journal of Basic Educational Research, 2025)
The low science literacy ability for Central Java Province is certainly related to educational institutions that produce prospective science teachers. The better and more mature the preparations are made, the more professional the graduates are produced. The purpose of this study is to reveal the phenomenon that occurs in an Islamic university in Surakarta as one of the producers of prospective MI teachers. The aspects measured include the essence of science and how to learn science. The data analysis technique uses descriptive statistics. The findings of this research are distinguished from three major challenges, namely (1) Specialization in the scientific field starts from the selection of science courses that are less accommodating to pay attention to the tendency of interest of prospective MI teachers, (2) the determination of courses should refer to the acquisition of science literacy assessments nationally and the rankings of PISA and TIMSS Indonesia, and (3) It is necessary to provide more intensive debriefing to prospective MI teachers about professionalism competencies.